2007
DOI: 10.1016/j.jhep.2007.01.040
|View full text |Cite
|
Sign up to set email alerts
|

Treatment with 2-AAF blocks the small hepatocyte-like progenitor cell response in retrorsine-exposed rats

Abstract: Background/Aims-Liver regeneration after partial hepatectomy (PH) in retrorsine-exposed rats is accomplished through proliferation and differentiation of small hepatocyte-like progenitor cells (SHPCs). The cells of origin of SHPCs are not known. We investigated the possibility that SHPCs are directly derived from oval cells, a known liver progenitor cell, by combining the retrorsine/PH (RP) model with 2-acetamidofluorene (2-AAF), an anti-mitotic agent that elicits an oval cell reaction in response to liver def… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
25
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 20 publications
2
25
0
Order By: Relevance
“…12 A definitive SHPC lineage marker does not exist, making it difficult to assess whether the regenerative responses observed in retrorsine-treated hepatitis B surface antigen transgenic mice are identical to those observed in retrorsine-exposed F344 rats. Based on data from our studies and others, 13,31 it seems likely that the hepatocyte clusters observed by Vig et al actually represent new hepatocyte progeny of oval cells rather than regenerative SHPCs. This supposition is bolstered by data in the current study that demonstrate that when oval cell-mediated regenerative responses are blocked through the use of DAPM, the SHPC-mediated regenerative response is unaffected, suggesting that oval cells are not the source of SHPCs.…”
Section: Discussionsupporting
confidence: 63%
See 3 more Smart Citations
“…12 A definitive SHPC lineage marker does not exist, making it difficult to assess whether the regenerative responses observed in retrorsine-treated hepatitis B surface antigen transgenic mice are identical to those observed in retrorsine-exposed F344 rats. Based on data from our studies and others, 13,31 it seems likely that the hepatocyte clusters observed by Vig et al actually represent new hepatocyte progeny of oval cells rather than regenerative SHPCs. This supposition is bolstered by data in the current study that demonstrate that when oval cell-mediated regenerative responses are blocked through the use of DAPM, the SHPC-mediated regenerative response is unaffected, suggesting that oval cells are not the source of SHPCs.…”
Section: Discussionsupporting
confidence: 63%
“…However, data from our recent studies show that retrorsine-resistant SHPCs are susceptible to 2-AAF poisoning. 13 In these studies, SHPCs were never found in the livers of 2-AAFtreated retrorsine-exposed animals at any time after PH, but clustering of new hepatocytes (oval cell progeny) occurred by 14 days post-PH. 13 The cellular response in 2-AAF-treated retrorsine-exposed rats is identical to that observed in 2-AAF/PH animals (in the absence of retrorsine), suggesting that the presence of retrorsine has no effect on oval cell-mediated liver regeneration, but that 2-AAF treatment blocks the outgrowth of SHPCs.…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…Obviously these cells could not be responsible for functional execution, especially during the immediate days post-PH. 50 Indeed, we found that a few BrdU-positive cells emerged at day 3 after operation; however, these cells might be the progenitor cells rather than the regenerating hepatocytes since they were much smaller and showed colony-like proliferation.…”
Section: Discussionmentioning
confidence: 71%